Developing junior doctors' prescribing practices through collaborative practice: Sustaining and transforming the practice of communities. Issue 2 (4th March 2017) - Noble, Christy; Brazil, Victoria; Teasdale, Trudy; Forbes, Mark; Billett, Stephen
ABSTRACT: Prescribing in acute healthcare settings is a complex interprofessional process with a high incidence of medication errors. Opportunities exist to improve prescribing learning through collaborative practice. This qualitative interview-based study aimed to investigate the development of junior doctors' prescribing capacity and how pharmacists contribute interprofessionally to this development and the prescribing practices of a medical community. The setting for this study was a large teaching hospital in Australia where ethical approval was gained before commencing the study. A constructionist approach was adopted and the interviews were held with a purposive sample of 34 participants including junior doctors ( n  = 11), clinical supervisors (medical; n  = 10), and pharmacists ( n  = 13). Informed by workplace learning theory, interview data were thematically analysed. Three key themes related to pharmacists' contributions to prescribing practices emerged: building prescribing capacities of junior doctors through guidance and instruction; sustaining safe prescribing practices of the community in response to junior doctor rotations; and transforming prescribing practices of the community through workplace learning facilitation and team integration. These findings emphasize the important contributions made by pharmacists to building junior doctors' prescribing capacities that also assist in transforming the practices of that community. These findings suggest that rather than developing more conventional education programs for prescribing, further consideration should be given to interprofessional collaboration in everyday activities and interactions as a means to promote both effective learning for individuals and advancing the enactment of effective prescribing practice.